Syntaxonomic diversity of ruderal vegetation along railways in the Minsk region - Vasiuk, Snezhana; Kulikova, Elena (Journal of the Belarusian State University. Ecology, 2026)
Railway vegetation is of great interest as a new anthropogenic habitat for grass communities, which spread not only along railway tracks but also along other communication structures. Research in this area is aimed at gaining new knowledge about the diversity and characteristics of plant communities forming along railways, as well as their role in the modern landscape. Studying the vegetation cover of railways will make it possible to predict and regulate the spread of introduced, potentially invasive species, with the subsequent development of measures for monitoring and managing adventitious plant species. The aim of the study was to characterize the syntaxonomic diversity of the ruderal vegetation formed along the railways of the Minsk region. Field studies were conducted between 2021 and 2024 using standard geobotanical methods at 15 key sites. Three habitat groups were identified in the study areas: railway tracks, embankments, and right-of-way strips. The t-SNE method and cluster analysis were used to identify and differentiate plant communities. The ecological and floristic classification of vegetation was performed using the Braun-Blanke method. The analysis revealed that the syntaxonomic diversity of ruderal vegetation along railways in the study area is represented by three classes (Sisymbrietea Gutte et Hilbig 1975, Artemisietea vulgaris Lohmeyer et al. in Tx. ex von Rochow 1951 and Epilobietea angustifolii Tx. et Preising ex von Rochow 1951), three orders, three unions, six associations, and two association variants. The developed system of syntaxa allows determining the ecological characteristics and nature of succession of grass communities in different types of railway habitats. Thus, along the railway tracks, under conditions of high anthropogenic pressure, xerophytic communities of the Linario – Brometum tectorum Knapp 1961 association (ass.) are formed, representing the initial stages of restorative succession. Mesophytic communities of the order Agropyretalia intermedio-repentis T. Müller et Görs 1969 of the class Artemisietea vulgaris (ass. Convolvulo arvensis – Elytrigietum repentis Felföldy 1943, Pastinaco sylvestris – Elytrigietum repentis Ishbirdin in Ishbirdin et al. 1988 and Arrhenathero elatioris – Dactylidetum glomeratae Arepieva 2015) are widespread on embankments and right-of-way strips, representing semi-natural grass phytocenoses. Nitrophytic communities of the class Epilobietea angustifolii (ass. Elytrigio repentis – Aegopodietum podagrariae Tuxen 1967 and Chaerophylletum aromatici Neuhauslova-Novotna et al. 1969) develop on more humid substrates of embankments and right-of-way strips with low environmental disturbance.